Critical Thinking Implied to Fashion Research Competencies - Nining Tristanti; Juliarti; Dita Dwi Nitami (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills are one of the demands that a learner must have which is expected to have an impact on skills (psychomotor). However, the critical thinking aspect is often an ability that is sometimes difficult for learners to achieve, especially if it is related to psychomotor tasks in learning fashion research during a pandemic. This study was conducted to improve thinking skills that can be used to increase competence in conducting student fashion research in the form of students' abilities in conducting design research to identify clearly and concretely. The stages of the process that must be passed cognitively in learning are the first; information as an initial stage of acquiring knowledge, second; transformation to understand, digest and analyze knowledge to be transformed into a new form, third; evaluation to find out the truth of the transformation results that have been carried out. The method used is Research and Development by adapting the stages of the Four D Model. The ten stages are simplified into 4 stages, Define, Design, Development and Dissemination. Implementation and Evaluation statistical tests, measuring the critical thinking competence of students found an increase in the Gain Score of 16.18%. The psychomotor aspect, the student performance competence in the Fashion Research project assignment has increased by 12.00%. This research conducts on student learning outcomes which apply critical thinking and psychomotor tests in the fashion research class. Critical thinking skills use mind map strategies (spider diagrams) in formulating problems that lead to students' ideas. The research instrument employ various tests implementing the principles of critical thinking and psychomotor learning outcomes. Material of Fashion Research Learning use E-book. The result of this study is an evaluation to measure the critical thinking skills of learners to elaborate problems, discover solutions, and generate ideas leading fashion design concepts.